The Influence of Perceived Service Quality on Service Quality - Sabri Yunus; Violinthika Harmawan (Pt. Threeple Herphi Educate, 2025)
The hospitality industry places service quality as a central determinant of guest satisfaction and competitiveness. This study aims to examine the influence of perceived service quality on overall service quality at Aston Batam Hotel & Residence, Indonesia. A quantitative causal–associative research design was employed, with a total of 100 valid responses collected through purposive sampling of hotel guests. Perceived service quality was measured through three indicators—staff performance, service processes, and service availability—while service quality was assessed using the SERVQUAL dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using SPSS 26.0, including assumption testing, linear regression, and coefficient of determination analysis. The results revealed that perceived service quality has a positive and significant effect on service quality (β = 1.531; t = 21.480; p < 0.001), with an R² value of 0.825, indicating that 82.5% of the variance in service quality is explained by perceived service quality. Staff performance and service processes emerged as the strongest perceived indicators, while responsiveness and assurance were the dominant service quality dimensions. The findings confirm the theoretical role of perceived service quality as a critical antecedent of service quality in the hospitality sector and provide managerial implications for hotel operators to strengthen employee training, streamline service processes, improve supporting facilities, and integrate service quality management with online reputation monitoring to sustain competitiveness and customer loyalty.